A pedagogy of digital identities: identity as a conceptual lens for teaching socio-technical justice - Jenna Condie; Luigi Di Martino; Benjamin Hanckel; Thilakshi Mallawa Arachchi; Bhavya Chitranshi (Digital Culture & Education)
Given the complexities and inequities of our digitised lives, many educators are developing technology curricula with an orientation towards social justice outcomes. Our pedagogical goals are to centre issues of digital inequalities, power, and social justice in curriculum about digital technologies. To do this, we use ‘identity’ as a conceptual lens and narrative for students to critically examine digital technologies. Drawing on a duo-ethnographic method, we examine the development of our ‘Digital Identities’ curriculum over an eight-year period, which encompasses teaching practices that make visible and aim to challenge the inequalities and inequities perpetuated by digital technologies and systems. A ‘pedagogy of digital identities’, we argue, positions students to explore the implicit assumptions embedded in technological design, reflexively consider their own digital identities, practices, and experiences of power, as well as (re)consider the socio-technically (un)just implications of our digitalising society.